2010
DOI: 10.1007/s00432-010-0914-8
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab enhances chemosensitivity of hepatocellular carcinoma to adriamycin related to inhibition of survivin expression

Abstract: These results implicate the bevacizumab-increased efficacy of adriamycin via an inhibition of survivin expression in malignant cells as well as tumor vasculature cells, which provides other insights into the mechanism of enhanced efficacy by combination of VEGF blocker and chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
10
0
1
Order By: Relevance
“…In conclusion, this study, together with previously reported results (13)(14)(15), indicates that combination therapy using bevacizumab as a key drug might be a promising regimen for the treatment of HCC. In a bevacizumab-based combination therapy regimen, ACR, which successfully improves HCC patient survival by preventing recurrence (17,18), is a preferred partner for bevacizumab because the combination of these agents significantly suppresses the growth of HCC xenografts by inhibiting cell proliferation and inducing apoptosis in HCC cells.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In conclusion, this study, together with previously reported results (13)(14)(15), indicates that combination therapy using bevacizumab as a key drug might be a promising regimen for the treatment of HCC. In a bevacizumab-based combination therapy regimen, ACR, which successfully improves HCC patient survival by preventing recurrence (17,18), is a preferred partner for bevacizumab because the combination of these agents significantly suppresses the growth of HCC xenografts by inhibiting cell proliferation and inducing apoptosis in HCC cells.…”
Section: Discussionsupporting
confidence: 75%
“…We consider the suppressive effect of this combination therapy on the tumor growth to be possibly associated with the inhibition of Akt phosphorylation because the activation of phosphatidylinositol 3-kinase (PI3K)/Akt signaling plays a critical role in the survival and proliferation of HCC cells and, therefore, targeting this signaling might be an effective strategy for the treatment of HCC (38,39). A recent experimental study showed that bevacizumab enhances the chemosensitivity of HCC by inhibiting the VEGF-PI3K/Akt signaling pathway (14). Phosphorylation of Akt is also one of the targets by which ACR suppresses the growth of HCC cells (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In HCC, its activity as a single agent or in combination has been suggested in several phase 2 studies. 6,7,[16][17][18] Interestingly, a randomized phase 3 study presented in abstract form showed that the combination of oxaliplatin and fluorouracil (FOLFOX4) is more effective and less toxic compared with the more traditional cytotoxic chemotherapy agent doxorubicin in advanced and metastatic HCC. 19 Our data demonstrate good tolerability as well, with mild to moderate grade 3/4 toxicity (<10% hematologic grade 3/4 toxicities), which is less than what is seen with other combination regimens with relatively newer chemotherapy agents, [19][20][21] despite a relatively less optimal performance status patient population in our study.…”
Section: Discussionmentioning
confidence: 99%